Analisis Spasial Breeding Places Potensial Aedes sp di Desa Bangunharjo, Sewon, Bantul, DIY - Ulfa Widiastuti; Sarjito Eko Windarso; Agus Kharmayana Rubaya (Sanitasi: Jurnal Kesehatan Lingkungan, 2021)
DHF is an endemic disease that spreads massively throughout the year, especially in the rainy season. It needs a method that can depict the spread of dengue cases based on the map of Ae-des sp. distribution. The aim of the study is to find out the spatial description of potential breeding places of Aedes sp. at Bangunharjo village, in Sewon, Bantul, DIY, by conducting a descriptive study with survey method. The study was held between January-April 2020. As the study popula-tion was 39 houses of DHF cases in 2019, meanwhile as the sample were 16 houses of dengue cases during two trimesters (May-December) in 2019 that met the criteria. The examination used visual larvae survey method, and to record the houses’ coordinates was by using GPS based on the presence of larvae. The study results show that the distribution of dengue cases in Bangun-harjo Village were occuring in all dukuh and tends to spread throughout the villages. This DHF mapping become a guide to see the presence of larvae at 50 m and 100 m distance from the cases’ houses based on possible breeding sites Aedes sp. The results also exhibit that the distri-bution of larvae in Bangunharjo Village as many as 40 houses (37,03 %) out of the observed 108 houses. The distribution of larvae using buffer method based on the type of containers, reveal that larvae distribution is found mostly in containers that used for daily purposes. The buffer ana-lyses find that DFH transmission at 50 m radius zone from cases’ point is more at risk to occur because more larvae are found